Peran Mahasiswa Universitas Jenderal Soedirman terhadap Pemberdayaan Ekonomi Masyarakat - Adhika Ayu Junantiar; Novita, Elly; Anggraeni, Oki; Rahajuni, Dijan (Edukasi IPS, 2025)
This study aims to analyze the role of students of Universitas Jenderal Soedirman in community economic empowerment through their support for the growth of Micro, Small, and Medium Enterprises (MSMEs) in the Grendeng area, North Purwokerto. The Grendeng area was selected due to its relatively high concentration of MSMEs and its geographical proximity to the Unsoed campus. This research employed a qualitative method through observation and in-depth interviews with MSME actors and students involved in related activities. The results indicate that the presence and activities of students in the area contribute to increased demand for MSME products, act as collaborative partners, and serve as promotional agents for MSME actors in sectors such as food businesses, photocopy services, boarding houses, and laundry services. These findings emphasize that students’ contributions can serve as a strategic and sustainable local economic force.